Credibility is Key: How Board Independence Translates ESG Disclosure into Firm Value in Indonesia (E-Jurnal Akuntansi, 2026)
This study examines the impact of Environmental, Social, and Governance (ESG) disclosure on firm value and the moderating role of board independence in an emerging market. Using Moderated Regression Analysis on 675 firm year observations from non-financial companies on the Indonesia Stock Exchange (2017-2023), the results reveal that ESG disclosure positively affects firm value. Furthermore, board independence significantly amplifies this relationship. This highlights that in emerging markets like Indonesia, robust governance is essential to translate sustainability reporting into credible, tangible corporate value. The findings suggest managers should integrate ESG strategies with strong independent oversight, and investors should evaluate governance quality to verify the credibility of a firm's sustainability initiatives.
Keywords: ESG Disclosure; Firm value; Board Independence; Corporate governance; Emerging market